Rediseño de la Unidad Educativa Dr. Pio Jaramillo Alvarado aplicando arquitectura lúdica en Cerecita Guayas - Morales Navarro, Julissa Mayerly (2025)
The purpose of the project is to create an educational space that is effective, functional and aesthetically pleasing for the entire parish of Cerecita located in the Mamey commune. To do this, data collection was carried out in order to identify the needs of the inhabitants. In addition, a study was carried out focused on determining the priority areas for implementation in the redesign of the Dr Pio Jaramillo Alvarado school. The redesign of the school is based on addressing the key needs to promote interactive learning, organizing the space into various zones: learning, different spaces were incorporated that allow the interaction of children to enhance their education effectively. The recreation and lounging area includes a variety of games along with seating areas. The administrative area is intended for offices, while the service area has sanitary facilities and warehouses.......